Essential Knowledge for Transistor-Level LSI Circuit Design - Nakura, Toru.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book is a collection of the miscellaneous knowledge essential for transistor-level LSI circuit design, summarized as the issues that need to be considered in each design step. To design an LSI that actually functions and to be able to properly measure it, an extremely large amount of diverse, detailed knowledge is necessary. Even though one may read a textbook about an op-amp, for example, the op-amp circuit design may not actually be possible to complete in one's CAD tools. The first half of this text explains important design issues such as the operating principles of CAD tools, including schematic entry, SPICE simulation, layout and verification, and RC extraction. Then, mistake-prone topics for many circuit design beginners, resulting from their lack of consideration of these subjects, are explained including IO buffers, noise, and problems due tothe progress of miniaturization. Following these topics, basic but very specialized issues for LSI circuit measurement are explained including measurement devices and measurement techniques. Readers will have the simulated experience of the whole flow from top to bottom of circuit design and measurement. The book will be useful for newcomers to a lab or to new graduates who are assigned to a circuit design group but have little experience in circuit design. This published work is also ideal for those who have some experience in circuit design, to confirm and complement the knowledge that they already possess.
Schematic Entry -- SPICE Simulation -- Layout and Verification -- Interconnect RC Extraction -- IO Buffers -- Noise -- Problems due to the Progress of Miniaturization -- Measurement Devices -- Measurement Techniques We -- The Overall Design Procedure.
Keywords: Electronic circuits; Computer science -- Mathematics; Electronic Circuits and Systems; Mathematical Applications in Computer Science